STRENGTHENING NATIONAL IDENTITY THROUGH EDUCATION ON THE RUPIAH CURRENCY AND SIMULATED “MINI STORE” PURCHASE AND SALE TRANSACTIONS: A STUDY OF PPWNI STUDENTS IN KLANG, SELANGOR, MALAYSIA - Cipta Kusumaningrum; Sri Luayyi; Anita Sumelvia Dewi (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
Strengthening national identity is an important aspect for students of Indonesian Schools Abroad, especially in the context of understanding state symbols such as the Rupiah currency. This community service activity aims to increase the knowledge, understanding, and attitude of nationalism among PPWNI Klang students in Selangor, Malaysia through Rupiah currency education and mini-store-based buying and selling transaction simulations. The methods used include interactive education on the characteristics, functions, and value of the Rupiah currency, as well as hands-on practice through simulated buying and selling transactions designed to resemble simple economic activities. This activity involves students as active subjects so that learning is contextual and enjoyable. The results of the activity showed an increase in students' understanding of the Rupiah currency, the function of money in everyday life, and the growth of pride and attachment to Indonesia's national identity. The Mini Store simulation proved to be an effective medium for applied learning in instilling national values and basic financial literacy. Thus, this program can be an alternative model for strengthening national identity for Indonesian students abroad through an educational and practical approach.